2016
DOI: 10.1017/s1092852916000432
|View full text |Cite
|
Sign up to set email alerts
|

Treatment recommendations for DSM-5–defined mixed features

Abstract: The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) mixed features specifier provides a less restrictive definition of mixed mood states, compared to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR), including mood episodes that manifest with subthreshold symptoms of the opposite mood state. A limited number of studies have assessed the efficacy of treatments specifically for DSM-5-defined mixed features in mood disorders. As such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
1
16
0
1
Order By: Relevance
“…The presence of manic/hypomanic symptoms during a depressive episode is associated with a higher rate of anxiety and substance use disorders, increased suicidality, greater impairment in functioning, more frequent family history of bipolar disorder, and poorer response to treatment 62 . It has been suggested that patients with mixed features who are treated with antidepressants should be monitored closely because they are at greater risk for emergence of activation, hypomania and suicidality 64 . An expert panel of mood disorder researchers, while acknowledging the limited number of prospectively designed trials for depression with mixed features, recommended atypical antipsychotic medication as the first-line treatment 65 .…”
Section: Clinical Subtypesmentioning
confidence: 99%
“…The presence of manic/hypomanic symptoms during a depressive episode is associated with a higher rate of anxiety and substance use disorders, increased suicidality, greater impairment in functioning, more frequent family history of bipolar disorder, and poorer response to treatment 62 . It has been suggested that patients with mixed features who are treated with antidepressants should be monitored closely because they are at greater risk for emergence of activation, hypomania and suicidality 64 . An expert panel of mood disorder researchers, while acknowledging the limited number of prospectively designed trials for depression with mixed features, recommended atypical antipsychotic medication as the first-line treatment 65 .…”
Section: Clinical Subtypesmentioning
confidence: 99%
“…Participants with comorbid psychiatric conditions were eligible for IV ketamine treatment if their primary diagnosis was MDD or BD, meeting Stage 2, or higher (inadequate response to at least two antidepressant trials), 27 criteria for TRD (inadequate response to at least two antidepressant trials). 28,29 A small subpopulation of participants had a primary diagnosis of OCD or PTSD (Table 1).…”
Section: Participantsmentioning
confidence: 99%
“…Available evidence suggests that conventional antidepressants prescribed for an MDE with MFS provide a less reliable therapeutic outcome, higher rates of non-remission, and intolerability. 19 Prospective data evaluating the course of illness in individuals experiencing MFS indicate that MFS has a much more pernicious illness trajectory (eg, earlier age at onset, greater episode frequency, higher rates of comorbidity and suicidality). Prescription data indicate that a significant percentage of individuals experiencing an MDE with MFS are treated with antipsychotic agents (first-and second-generations), as well as traditional mood stabilizers (eg, lithium).…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, MFS has not been rigorously studied with sufficient randomized, double-blind, placebo-controlled trials. Available evidence suggests that conventional antidepressants prescribed for an MDE with MFS provide a less reliable therapeutic outcome, higher rates of non-remission, and intolerability 19 . Prospective data evaluating the course of illness in individuals experiencing MFS indicate that MFS has a much more pernicious illness trajectory (eg, earlier age at onset, greater episode frequency, higher rates of comorbidity and suicidality).…”
Section: Introductionmentioning
confidence: 99%